Retroactive changes should be introduced in the Code only with great care: problems related to the spellings of nomina - Dubois, Alain (Zootaxa, 2010)
Taxonomy is currently facing a major crisis and is likely to have strong difficulties to reduce significantly the taxonomic gap before the biodiversity crisis has wiped out a large proportion of the living species of the earth. In this context, taxonomists should pay great attention to the nomenclatural Rules, and care for them to help them in this urgent task, rather than diverting their time and energy to secondary or useless questions or debates. A major purpose of the Code is to promote nomenclatural stability in zoology. This requires stability in the Rules, or at least that a great care be taken, when establishing new Rules, to avoid that they can have unexpected deleterious consequences for stability. In particular, in most cases, it is crucial to deny retroactivity to the new Rules. Several examples of problems created in zoological nomenclature by introduction of changes in Articles dealing with the spellings of nomina are examined in detail. These Articles were modified, with retroactive value, in the 1985 edition (Art. 32, 33, 35 and 39) and in the 1999 edition (Art. 24) of the Code. It is shown that these changes, which have no clear “philosophical” or practical justifications and which result in no clear benefits, have in fact had negative impacts on nomenclatural practice. Their implementation requires heavy useless additional work from taxonomists and has negative results in nomenclatural stability that had clearly not been anticipated by the ICZN when promulgating them. In a few sets of nomina tested below, the changes in the 1985 edition resulted in spelling changes for 10.0 to 22.2 % of the nomina, and those in the 1999 edition for 21.7 to 33.3 % of the nomina, roughly a quarter of them on the whole (24.5 %). Among others that are less emblematic, a striking case is that of the fish generic nomen Tetraodon, widely used especially since the genome of a species of this genus has been sequenced, and which should be changed to Tetrodon because of the unwarranted introduction of the new Art. 24.2.4 into the Code. It is suggested that these changes should be cancelled, or at least denied retroactivity from the years of their promulgations. In order to make this discussion easier, a “taxonomy” of the different kinds of spellings of nomina, and a dichotomic key to such situations, are provided. This stresses the fact that detailed discussions on very precise aspects of the functioning of nomenclatural Rules, as well as the computerization of nomenclatural data for online databases, require to use a specialized technical terminology to designate the nomenclatural concepts and tools, not vague “common language” terms like “name” or “type”: “keep the Rules, but change the terms”. The problems outlined here should be kept in mind by the ICZN before implementing drastic changes in the Rules of nomenclatural availability, as recently suggested.